1984
DOI: 10.1159/000123988
|View full text |Cite
|
Sign up to set email alerts
|

Central Electrophysiologic Correlates of Pulsatile Luteinizing Hormone Secretion in the Rhesus Monkey

Abstract: Characteristic increases in neuronal activity coincident with the pulsatile release of luteinizing hormone from the pituitary gland have been recorded from electrodes chronically implanted in the medial basal hypothalamus of the rhesus monkey. This electrophysiologic manifestation of the hypothalamic ‘pulse generator’ which governs the secretion of hypothalamic luteinizing hormone releasing hormone provides, for the first time, direct access to the central component of the neuroendocrine control system which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
140
1
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(153 citation statements)
references
References 18 publications
10
140
1
2
Order By: Relevance
“…In such studies, inter-GnRH-pulse intervals of approximately 1 h have been described for juvenile ovariectomized monkeys . In adult ovariectomized monkeys, direct and indirect assessment of GnRH pulse frequency has yielded comparable estimates of this parameter, namely approximately 1 pulse/h (Dierschke et al 1970, Wilson et al 1984, Gearing & Terasawa 1991. Since the present indirect analysis of GnRH pulse frequency in the prepubertal animal employed a pituitary with a responsiveness similar to that in the adult, the lack of congruency between the results obtained by the two methods in the prepubertal state must therefore be related to the smaller GnRH signal at this stage of development.…”
Section: Discussionmentioning
confidence: 72%
“…In such studies, inter-GnRH-pulse intervals of approximately 1 h have been described for juvenile ovariectomized monkeys . In adult ovariectomized monkeys, direct and indirect assessment of GnRH pulse frequency has yielded comparable estimates of this parameter, namely approximately 1 pulse/h (Dierschke et al 1970, Wilson et al 1984, Gearing & Terasawa 1991. Since the present indirect analysis of GnRH pulse frequency in the prepubertal animal employed a pituitary with a responsiveness similar to that in the adult, the lack of congruency between the results obtained by the two methods in the prepubertal state must therefore be related to the smaller GnRH signal at this stage of development.…”
Section: Discussionmentioning
confidence: 72%
“…This mechanism is essential to prevent both secretory machinery fatigue and target tissue desensitization. Although early evidence suggested that secretory pulses mirror the intermittent bursts of electrical activity exhibited by hypothalamic neuroendocrine cells 1,2 , the mechanisms that produce this pulsatility remain poorly understood, and several non-competing hypotheses are proposed. For example, the ultradian hourly rhythm in the activity of the hypothalamopituitary-adrenal axis may primarily reflect sub-hypothalamic endocrine feedforward-feedback mechanisms 3 .…”
mentioning
confidence: 99%
“…5). A synchronous and intermittent discharge of multiple GnRH neurons (6) is required for episodic increases in the concentration of GnRH in hypophyseal portal blood. This intermittent secretion is the result ofan oscillator, the so-called GnRH pulse generator, localized in the mediobasal hypothalamic-anterior hypothalamic-preoptic area (7)(8)(9).…”
mentioning
confidence: 99%
“…In both the rat (7) and monkey (8) surgical deafferentation of the mediobasal hypothalamus does not interfere with GnRH pulses. Lesions of the arcuate nuclei in primates, which destroy many of the GnRH neurons, abolish the ultradian pattern of release, and neural activity within this region has been correlated with the pulses (6,9). Furthermore, superfused hypothalamic fragments in vitro release GnRH in a pulsatile fashion (10).…”
mentioning
confidence: 99%